Bariatric surgery reverses ventricular repolarisation heterogeneity in obesity: mechanistic insights into fat-related arrhythmic risk. (3rd October 2022) - Patel, K; Bajaj, N; Statton, B; Li, X; Herath, N S; Nyamakope, K; Davidson, R; Stoks, J; Purkayastha, S; Ware, J S; O'Regan, D P; Lambiase, P D; et al.
Abstract: Background: Obesity is a growing global health problem that confers higher risks of atrial arrhythmias and sudden cardiac death. Despite this, the proarrhythmic substrate in obesity and its reversibility with weight loss has not been studied in-depth. Purpose: To characterise the proarrhythmic substrate in obese patients, and its reversibility with bariatric surgery, using electrocardiographic imaging (ECGi). Methods: ECGi was performed in 16 obese patients pre-bariatric surgery (PreSurg; mean age 43±12 years, 13 female) and 16 age- and sex-matched non-obese (lean) individuals (42±11 years). 12 of the 16 obese patients also underwent ECGi after bariatric surgery (PostSurg). Over 2000 atrial and ventricular epicardial electrograms were computed using high density body surface mapping (256-lead ECG) and heart-torso geometries from cardiac magnetic resonance imaging, by solving the inverse problem of electrocardiography. Local atrial and ventricular epicardial activation times (AT) were calculated as the steepest downslope of their respective activation complexes, and local ventricular repolarisation times (RT) as the steepest upslope of the T-wave. Atrial activation gradients (ATG) and ventricular repolarisation gradients (RTG) were calculated as the maximum difference within 10 mm radius divided by the corresponding distance. Results: Body mass index was greater in PreSurg vs lean (46.7±5.5 vs 22.8±2.6 kg/m 2, p<0.0001) and decreased with surgery (PostSurg 36.8±6.5 kg/m 2, p<0.0001). Epicardial adipose tissue (EAT) was greater in PreSurg vs lean (83±56 vs 28±13 ml, p<0.0001) and decreased post-surgery (PostSurg 69±45 ml, p=0.0010). Total atrial AT was prolonged in PreSurg vs lean (62±15 vs 46±12 ms, p=0.0028), which persisted post-surgery (PostSurg 67±15 ms, p=0.86). Atrial ATG were also greater in PreSurg vs lean (26±11 vs 14±8 ms, p=0.0007) and did not change with weight loss (PostSurg 25±12, p=0.44). Ventricular RTG were greater in PreSurg vs lean (26±11 vs 15±7 ms/mm, p=0.0024) and decreased with weight loss (PostSurg 19±8, p=0.0009). Ventricular RTG were similar between PostSurg and lean (p=0.20). EAT from lean and PreSurg individuals correlated with atrial ATG (r=0.36, p=0.044) and ventricular RTG (r=0.54, p=0.0014). Ventricular AT were similar between lean (31±6 ms), PreSurg (34±5 ms) and PostSurg (35±9 ms); all p>0.05. Conclusion: Steep ventricular repolarisation gradients and prolonged atrial activation contribute to the proarrhythmic substrate in obesity. Ventricular repolarisation gradients correlate with epicardial adiposity and both regress post-bariatric surgery. By contrast, atrial activation remains prolonged after weight loss. These results provide mechanistic insights into obesity-related arrhythmic risks and their reversibility with weight loss following bariatric surgery. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): British Heart FoundationNational Institute for Health Research (NIHR) Imperial Biomedical Research Centre (BRC).